Twist and turn of an unusual entity: A rare case report of torsion of huge epididymal cyst from a tertiary hospital - Manojit Sarkar,; Arup Kumar Ghosh,; Purnendu Dutta,; Amit Ray, (Asian Journal of Medical Sciences, 2024)
An epididymal cyst (EC) is a benign lesion. It arises due to cystic degeneration of the epididymis. The torsion of it is extremely rare. The usual presentation of the cyst is asymptomatic scrotal swelling. The swelling has a lobulated surface and feels like a bunch of grapes. The huge EC is rare and moreover, it is associated with torsion-rarest presentation.